Ethnography and journalism : Transdisciplinary uses and borders - Giménez Delgado, Inés (InMediaciones de la Comunicación, 2023)
This article reflects on the amphibious and transdisciplinary ways of doing anthropology and journalism. Based on a qualitative, reflexive and inductive methodology that draws from fieldwork experiences in the Mexican southwest and from the review of journalistic and ethnographic works, the article analyses the meeting points and the differences between both disciplines in an era influenced by hybridization, transmutation, and hyperspecialization of the fields of knowledge. Likewise, it reflects on the transformative power of transdisciplinary studies in situations of armed conflict and extreme violence, where the testimony and the experience of the body as a witness need other disciplines –between literature and the pure sciences– to strengthen the locus of enunciation. Finally, it explores whether the hybrid uses made of journalistic-anthropological narration have generated polyphonic discourses that, from their trans condition, allow overcoming the hyper-presentism that traps a good part of journalism and bridge the temporal distance of the colonial matrix from which anthropology historically constructed its object of study.